The Intervention Package Increases the Readiness of Health Post Cadres to Preventing Stunting in Children - Erna Julianti; Elni Elni (Universitas Aisyah Pringsewu, 2023)
Stunting is one of the priority nutrition problems in Indonesia. The incidence of stunting in 2018 to 2021 has decreased but has not yet reached the government's target of 14.4%. The intervention of stunting is very important to be done by nurses and the integrated health post cadres to prevent stunting. This study aimed to identify the effect of the stunting intervention package on the preparedness of health post cadres (knowledge and motivation) in stunting prevention. This study was a pra-experimental approach using pre-test and post-test without control. The number of samples was 30 respondents with the purposive sampling technique. The instruments in this study were characteristics and preparedness questionnaires. The health post cadre’s preparedness questionnaire consisted of a questionnaire on knowledge and motivation. The analysis used in this study was the Wilcoxon test. The average knowledge and motivation of health post cadres after the stunting intervention package were higher, with a value of 11.63 and 55.20, compared to those before the intervention which were 10.23 and 52.97. The results show a significant difference between the average knowledge and motivation of cadres in stunting prevention before and after the stunting intervention package was given with a p-value of 0.001 and 0.027. There is a significant difference between the average knowledge and motivation of health post cadres before and after being given the stunting intervention package. it is hoped that the cadres will consistently implement the stunting intervention package at the health post.